2005
DOI: 10.1371/journal.pgen.0010042
|View full text |Cite|
|
Sign up to set email alerts
|

AVPR1a and SLC6A4 Gene Polymorphisms Are Associated with Creative Dance Performance

Abstract: Dancing, which is integrally related to music, likely has its origins close to the birth of Homo sapiens, and throughout our history, dancing has been universally practiced in all societies. We hypothesized that there are differences among individuals in aptitude, propensity, and need for dancing that may partially be based on differences in common genetic polymorphisms. Identifying such differences may lead to an understanding of the neurobiological basis of one of mankind's most universal and appealing behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 71 publications
10
155
1
2
Order By: Relevance
“…Importantly, a recent study showed that a similar cellular mechanism might operate in humans by demonstrating differences in mRNA expression in human hippocampus between long and short alleles of RS3. 19 A further link to social behaviour in general was provided by the same group that found association of RS1-RS3 haplotypes with a personality trait, reward dependence 20 and an impact of long and short alleles of RS3 on altruistic behaviour during an economic game, the dictator game. 19 Finally, Prichard et al 21 found an association of AVPR1A polymorphisms with another phenotype related to social behaviour, age of first intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a recent study showed that a similar cellular mechanism might operate in humans by demonstrating differences in mRNA expression in human hippocampus between long and short alleles of RS3. 19 A further link to social behaviour in general was provided by the same group that found association of RS1-RS3 haplotypes with a personality trait, reward dependence 20 and an impact of long and short alleles of RS3 on altruistic behaviour during an economic game, the dictator game. 19 Finally, Prichard et al 21 found an association of AVPR1A polymorphisms with another phenotype related to social behaviour, age of first intercourse.…”
Section: Introductionmentioning
confidence: 99%
“…32 The dopaminergic and serotonergic systems have been shown to influence cognitive and motor functions in human and animal studies. 8,10,13,34,35 Neurophysiological studies have shown that listening to music has a strong impact on activity in a network of mesolimbic structures involved in reward processing. 34,35 We have previously studied the association between musical aptitude and creativity in music and the polymorphisms of the DRD2 (plus COMT and TPH1 genes), but did not found an association.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood with standard phenol-chloroform procedure. Genotyping of the highly variable microsatellites RS3 (corresponding to (CT) 4 -TT-(CT) 8 (GT) 24 ) and RS1 (corresponding to (GATA) 14 ) residing in the promoter region and AVR (corresponding to (GT) 14 (GA) 13 (A) 8 ) microsatellite in the intron of the AVPR1A gene was performed ( Figure 2). 22 The SLC6A4 promoter region 5-HTTLPR and the VNTR microsatellite were genotyped as described by Ukkola et al 8 Primer sequences are available on request from the authors.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on dopamine receptors were performed according to methods described by Treister et al (38) and those on serotonin transporter according to methods described by Bachner-Melman et al (39). In brief, they are as follows: DRD4 (38): The DRD4 exon III polymorphism was characterized using the following primers: DRD4 P1 5′-GGC GTT GCC GCT CTG AAT GC-3′ and DRD4 P2 5′-GAG GGA CTG AGC TGG ACA ACC-3′.…”
Section: Genetic Studiesmentioning
confidence: 99%